Microbiota Succession and Chemical Composition Involved in the Radish Fermentation Process in Different Containers - Liu, Lei; She, Xiao; Chen, Xing; Qian, Yang; Tao, Yufei; Li, Yalin; Guo, Shuyu; Xiang, Wenliang; Liu, Guorong; Rao, Yu (Frontiers in Microbiology, 2020)
Traditional Chinese fermented vegetables is a type of brine-salted fermented vegetable product. During the spontaneous fermentation, various compounds are produced, degraded, and converted, influencing the quality of the fermented pickle. To ascertain the effect of the different containers on the fermentation process of the pickles, this study investigated the bacterial diversity and the chemical composition characteristics of the pickle (radish) fermented in commonly used containers including glass jars (GL), porcelain jars (PO) and plastic jars (PL). The correlation between chemical compounds and and microbial community was further analyzed. The changes in pH values suggest that PL may facilitate the quickest fermentation of the pickles, while the process in PO progress at the lowest rate. The PL brine samples contain higher levels of lactic acid and threonine, while more abundant volatile chemical compounds are evident in PO. The container materials had no significant influence on the microbial structure. Lactobacillus was the absolute dominant genus in all containers. But it had effect on the abundance of specific genus, such as Lactococcus, Pediococcus and norank Chloroplast. The correlation between these major genera was also analyzed and gene function prediction indicated that the top three pathways were carbohydrate metabolism, amino acid metabolism, energy metabolism. Lactobacillus negatively correlated with methionine, tyrosine, lysine and arginine, while positively correlated with ammonia, and lactic acid and acetic acid both just correlated with Pediococcus. This study provides new insights into the microbiota succession and chemical compounds involved in the vegetable fermentation.